Socioeconomic inequality in unmet outpatient healthcare needs among people living in urban informal settlements in Sanandaj city, Iran - Bakhtiar Piroozi; Hossein Safari; Amjad Mohamadi Bolbanabad; Ghobad Moradi; Yadolah Zarezadeh; Azad Shokri; Farhad Moradpour (BMC, 2023)
Abstract Background The growing trend of informal settlements is a serious humanitarian crisis. Unmet need for health care services is an indicator to measure the state of equality and access to healthcare services. This study, for the first time in Iran, examined the prevalence of unmet needs for outpatient healthcare services and related socioeconomic inequalities among residents of informal settlements in Sanandaj city. Methods This cross-sectional study was conducted on informal settlements of Sanandaj city with a sample size of 1345 people. Data were collected using a questionnaire. Multivariate logistic regression was used to determine significant predictors of unmet needs for healthcare services. Concentration index (C) and concentration curve (CC) were calculated to measure inequality in the prevalence of unmet needs for healthcare services. Results The prevalence of unmet needs for outpatient healthcare services was 31.7%. Financial and physical barriers were the most common reasons for not using the needed services. The highest unmet need was related to dental (80.6%) and rehabilitation services (78.8%). Being elderly with about 2.3 times (OR: 2.37, 95% CI: 1.19-4.75), not having a job with about 1.7 times (OR: 1.70, 95% CI: 1.13-2.57) and having a low economic status with about 4 times (OR: 4.46, 95% CI: 2.39-9.70) increased the odds of experiencing unmet need for outpatient healthcare services. The value of concentration index showed that unmet need for outpatient healthcare services was significantly concentrated among people with lower economic status (C= -0.330, 95% CI: -0.432 to -0.227). Conclusion The unmet need is high among people living in informal settlements of Sanandaj city and a significant part of the residents of these settlements does not have access to required healthcare services. Regardless of the needs of people living in these settlements, who constitute a large population of Iran, access to universal health coverage is not possible in such areas. Removing the identified obstacles and causes behind the unmet needs requires the interdisciplinary participation of all actors, including the government, the nation, and civil society.